PENGARUH PENERAPAN STRATEGI OUTSOURCING DAN STRATEGI CORE COMPETENCY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Dian Imanina Burhany (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
To survive and win in tight competitive business environment nowadays, a company must develop and implement the proper strategies. Strategy outsourcing, the strategy where company transferring some of organization’s activities to outside providers, and strategy core competency, the strategy where company concentrate its own resources on a set of core competencies, are two strategies can help company to improve its performance. The purpose of this research is to measure the effect of application strategy outsourcing and strategy core competency on company financial performance. The research is performed to nine BUMN which have head office on Bandung City. Respondents are the vice presidents and the heads of strategic planning department of the companies. Data analysis to test the hypothesis is multiple regression analysis by exercising software SPSS 12.0 for Windows. The result of this research shows that simultaneously application strategy outsourcing and strategy core competency have positive and significant effect on all financial performance indicators of BUMN which have head office on Bandung City. But partially, application strategy outsourcing has significant effect only on ROE and NPM indicators but has not significant effect on ROA indicator, while strategy core competency has not significant effect on all financial performance indicators